Productive and qualitative traits of Brachiaria decumbens pasture in monoculture and associated with Stylosanthes guianensis - Paciullo, Domingos Sávio Campos; Aroeira, Luiz Januário Magalhães; Alvim, Maurílio José; Carvalho, Margarida Mesquita (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the forage mass and botanical composition of Brachiaria decumbens Stapf pasture in monoculture and associated with Stylosanthes guianensis (Aubl.) Sw. var. vulgaris cv. Mineirão in various months along the year. The samples from January and May were rumen incubated. Three paddocks (replications) were divided in two plots (monoculture and associated pastures). After the evaluations forage was grazed by dried cows. The forage mass of B. decumbens did not vary with the pasture system; in October it was lower (291 kg/ha) and maintained stable along the other months (1,571 kg/ha). A decrease tendency of legume forage mass was observed during the experimental period. The proportion of S. guianensis in the pasture was higher in October/2001 and lower in January/2002. The total forage mass of associated pasture (2,158 kg/ha) was higher than the monoculture pasture (1,481 kg/ha). The degradation rates and effective degradability of S. guianensis and B. decumbens were respectively 6.8%/h and 61.5% and 5.3%/h and 49.2%. The legume contribute for higher quantity and better quality forage available in associated pasture.